Analisis Pengaruh Rasio Keuangan Dan Variabel Makro Ekonomi Terhadap Harga Saham (Studi Kasus Pada Perusahaan Perbankan Yang Masuk Dalam Indeks LQ45) - Rohmatun Nafiah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2019)
Investment is an alternative to anticipate future events. Therefore investment planning needs to be done. This study focuses on changes stock prices of banking companies included in the LQ45 index. Where companies included in the LQ45 index are companies that have high liquidity. This study uses ROE, EPS, DER and CAR as fundamental factors thats influence stock prices. While the exchange rate as macroeconomic factor that effect stock prices. The analysis method in this study uses linear multiple regression analysis. The results of the analysis show that return on equity (ROE) has no influence on stock prices, earning per share (EPS) has not significant and positive effect on stock prices, debt to equity ratio (DER) has a significant and negative effect on stock prices, capital adequecy ratio (CAR) has a significant and positive effect on stock prices and the exchange rate has no influence on stock prices.